Shikimate and Phenylalanine Biosynthesis in the Green Lineage - Tohge, Takayuki; Watanabe, Mutsumi; Hoefgen, Rainer; Fernie, Alisdair R. (Frontiers in Plant Science, 2013)
The shikimate pathway provides carbon skeletons for the aromatic amino acids L-tryptophan, L-phenylalanine and L-tyrosine. It is a high flux bearing pathway and it has been estimated that greater than 30% of all fixed carbon is directed through this pathway. These combined pathways have been subjected to considerable research attention due to the fact that mammals are unable to synthesize these amino acids and the fact that one of the enzymes of the shikimate pathway is a very effective herbicide target. However, in addition to these characteristics these pathways additionally provide important precursors for a wide range of important secondary metabolites including chlorogenic acid, alkaloids, glucosinolates, auxin, tannins, suberin, lignin and lignan, tocopherols and betalains. Here we review the shikimate pathway of the green lineage and compare and contrast its evolution and ubiquity with that of the more specialized phenylpropanoid metabolism which this essential pathway fuels.